Uv-Visible Microscope Spectrophotometric Polarization And Dichroism With Increased Discrimination Power In Forensic Analysis - Purcell, Dale Kevin (2013)
Microanalysis of transfer (Trace) evidence is the application of a microscope and microscopical techniques for the collection, observation, documentation, examination, identification, and discrimination of micrometer sized particles or domains. Microscope spectrophotometry is the union of microscopy and spectroscopy for microanalysis. Analytical microspectroscopy is the science of studying the emission, reflection, transmission, and absorption of electromagnetic radiation to determine the structure or chemical composition of microscopic-size materials. Microscope spectrophotometry instrument designs have evolved from monochromatic illumination which transmitted through the microscope and sample and then is detected by a photometer detector (photomultiplier tube) to systems in which broad-band (white light) illumination falls incident upon a sample followed by a non-scanning grating spectrometer equipped with a solid-state multi-element detector. Most of these small modern spectrometers are configured with either silicon based charged-couple device detectors (200-950 nm) or InGaAs based diode array detectors (850-2300 nm) with computerized data acquisition and signal processing being common. A focus of this research was to evaluate the performance characteristics of various modern forensic (UV-Vis) microscope photometer systems as well as review early model instrumental designs. An important focus of this research was to efficiently measure ultraviolet-visible spectra of microscopically small specimens for classification, differentiation, and possibly individualization. The first stage of the project consisted of the preparation of microscope slides containing neutral density filter reference materials, molecular fluorescence reference materials, and dichroic reference materials. Upon completion of these standard slide preparations analysis began with measurements in order to evaluate figures of merit for comparison of the instruments investigated. The figures of merit investigated included: 1) wavelength accuracy, 2) wavelength precision, 3) wavelength resolution stability, 4) photometric accuracy, 5) photometric precision, 6) photometric linearity, 7) photometric noise, and 8) short-term baseline stability. In addition, intrinsic instrument polarization effects were investigated to determine the impact of these properties on spectral interpretation and data quality. Finally, a set of recommendations were developed which describe instrument performance characteristics for microscope and spectrometer features and functions, and specific instrument parameters that must be controlled in order to acquire high quality data from an ultraviolet-visible forensic microscope spectrophotometer system for increased discrimination power